Understanding Women’s Social Participation in NGOs: A new framework discovered / Noorfadhleen Mahmud, Dr. Nadrawina Isnin and Dr. Noni Harianti Junaidi - Mahmud, Noorfadhleen; Isnin, Dr. Nadrawina; Junaidi, Dr. Noni Harianti (2021)
This is a new framework for women's social participation in NGOs, particularly for Malaysian women. This will contribute to a more concise framework on how to look and discuss the motivation, inhibiting factors, level of involvement and relates to women empowerment. This will indicate all the factors involved will contribute to women's empowerment perspectives. This new framework is part of the output gathered from the writer's PhD Thesis entitled Sarawak Women's Social Participation in Non- governmental Organization 2021, Universiti Teknologi MARA.